A new species of Ethobunus Chamberlin, 1925 (Opiliones: Zalmoxidae) from Oaxaca, Mexico, with taxonomic notes on Mexican species of the genus - Cruz-López, Jesús Alberto (Instituto de Ecología, A.C., 2020)
A new species of the genus Ethobunus Chamberlin, 1925 from Mexico is described: Ethobunus oaxacensis sp. nov. The description of this new species is based on both sexes, specimens collected from different localities of low deciduous forest in the coastal region from the state of Oaxaca. Ethobunus oaxacensis sp. nov. is compared with other two species of the genus present in Mexico: Ethobunus acanthotibialis (Goodnight & Goodnight, 1953) and Ethobunus pilosus (Goodnight & Goodnight, 1953); it is also compared with the most similar species, Ethobunus cubensis (Šilhavý, 1979) and Ethobunus kratochvili (Šilhavý, 1979), both from Cuba. Additional comments on the taxonomy of the Mexican Ethobunus and Pachylicus Roewer, 1923 are provided.